1965
DOI: 10.1111/j.1751-1097.1965.tb09300.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence Involving Peroxide Decompositions

Abstract: It is a reasonable assumption that many of the known cherniluminescent organic compounds react to give a carbonyl group in an excited state. By extension of this hypothesis we were led to test several substituted acridinium salts. Oxidation of these with hydrogen peroxide in the presence of base resulted in the formation of N-methylacridone in high yield, and the emission of light from an excited state of this ketone. Mechanisms for this process are discussed. Interest in indole derivatives aroused by the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 24 publications
2
26
0
1
Order By: Relevance
“…McCapra and Chang investigated light emitting reactions with different 2,3-disubstituted indoles and their 3-hydroperoxide derivatives, proposing a mechanism that explains the observed chemiluminescence and which is consistent with Witkop's mechanistic proposals for that type of reaction (Scheme 14) [30][31]. The deprotonated amide group 69*, that is formed by decomposition of the cyclic peroxide, slowly relaxes from its excited state and functions as a transmitter for the chemiluminescence reaction.…”
Section: Oxidation With Oxygenmentioning
confidence: 55%
“…McCapra and Chang investigated light emitting reactions with different 2,3-disubstituted indoles and their 3-hydroperoxide derivatives, proposing a mechanism that explains the observed chemiluminescence and which is consistent with Witkop's mechanistic proposals for that type of reaction (Scheme 14) [30][31]. The deprotonated amide group 69*, that is formed by decomposition of the cyclic peroxide, slowly relaxes from its excited state and functions as a transmitter for the chemiluminescence reaction.…”
Section: Oxidation With Oxygenmentioning
confidence: 55%
“…Theoretical results have indicated that charge‐transfer processes should also be observed for CL systems containing no electron‐rich moiety . Moreover, the presence of oxidizable electron‐rich moieties are insufficient for the efficient formation of singlet excited states, in both intra‐ and intermolecular CL reactions …”
Section: The Molecular Mechanisms Of Chemiluminescencementioning
confidence: 99%
“…We had earlier 22 chosen certain acridine derivatives as an easily studied series of chemiluminescent compounds. This series would appear to be among the least ambiguous and best understood of the examples of organic chemiluminescence at the present time.…”
Section: Chemiluminescence From Peroxide Decompositionmentioning
confidence: 99%